Mengungkap tren teknologi digital dalam pendidikan Islam: tinjauan bibliometrik publikasi ilmiah internasional bereputasi - Mannan, Abd; Tamami, Badrut; Syaifudin, Mokhamad; Niam, Khoirun (TA`DIBUNA, 2025)
Digital transformation in Islamic education has become a crucial topic since the COVID-19 pandemic, yet systematic analyses remain limited. This study analyzes scholarly publication trends on digital transformation in Islamic education using a bibliometric approach based on 227 publications from the Scopus database (2019–2024), employing VOSviewer to map thematic networks and collaborations. The findings show a significant increase in publications since 2023, with Indonesia and Malaysia as the main contributors. Keywords such as "Islamic education" and "e-learning" dominate the research landscape, while institutions like Universiti Malaya and Universitas Pendidikan Indonesia make notable contributions. The implications of this research include new opportunities such as integrating AI-based technologies into the Islamic education curriculum and enhancing cross-country collaborations. This study provides a clear map of trends, patterns, and thematic relationships, offering strategic insights for academics and policymakers to more effectively integrate technology into Islamic education. AbstrakTransformasi digital dalam pendidikan Islam menjadi topik krusial sejak pandemi COVID-19, namun analisis sistematis terkait masih minim. Penelitian ini menganalisis tren publikasi ilmiah tentang transformasi digital dalam pendidikan Islam melalui pendekatan bibliometrik terhadap 227 publikasi dari database Scopus (2019–2024), menggunakan VOSviewer untuk memetakan jaringan tematik dan kolaborasi. Hasilnya menunjukkan peningkatan signifikan publikasi sejak 2023, dengan Indonesia dan Malaysia sebagai kontributor utama. Kata kunci seperti Islamic education dan e-learning mendominasi, dan institusi seperti Universiti Malaya serta Universitas Pendidikan Indonesia memberikan kontribusi penting. Implikasi penelitian ini meliputi peluang riset baru, seperti integrasi teknologi berbasis AI dalam kurikulum pendidikan Islam dan peningkatan kolaborasi lintas-negara. Studi ini memberikan peta tren, pola, dan hubungan tematik yang bermanfaat bagi akademisi dan pembuat kebijakan untuk integrasi teknologi yang lebih efektif dalam pendidikan Islam.